Addition of Lithium Iodide into Precursor Solution for Enhancing the Photovoltaic Performance of Perovskite Solar Cells. Issue 10 (27th July 2017) - Luo, Hui; Wu, Jihuai; Liu, Quanzhen; Huang, Jianling; Tu, Yongguang; Lin, Jianming; Huang, Miaoliang
Abstract: Lithium iodide is mixed into the perovskite precursor solution as an additive. X‐ray diffraction, field‐emission scanning electron microscopy, steady‐state photoluminescence, ultraviolet–visible absorption spectra, and electrochemical impedance spectra are used to characterize and analyze the perovskite solar cells prepared from this solution. It is found that the LiI additive can improve the crystallinity and the quality of perovskite crystal, enhance the light absorbance and the charge carrier extraction of the perovskite films, and reduce the charge‐transfer resistance of the device. As a consequence, the open‐circuit voltage and the fill factor of the perovskite solar cells increase. Under optimal conditions, the LiI‐containing perovskite solar cell can achieve a power conversion efficiency of 16.53 % whereas the device based on a perovskite without added LiI has an efficiency of 14.22 % under the same experimental conditions. The simple process and significant improvement in the performance render this method promising. Abstract : Into the Mix : Lithium iodide is introduced as an additive to the perovskite precursor solution. The addition effects the crystal growth of perovskite film, giving rise to increased crystallinity, which improves the quality and conductivity of the perovskite film and speeds up the charge transport in the device. The perovskite solar cell utilizing LiI gives rise to a power conversion efficiency that is considerably higher than a device based on a perovskite without added LiI.